Socialization of Financial Management to Gondang Vocational High School Students - Anisa Kamila; Nailatul Adwiyah; Sheylomitha Suryaning Putri; Hendri Hermawan Adinugraha; Ria Anisatus Sholihah (Peneliti Teknologi Teknik Indonesia, 2023)
Financial management is all activities related to the management of finances and financial assets. Currently, many students do not know how to manage finances, so this socialization is needed so that students can manage their finances properly. This article aims to provide an understanding of personal financial management to 10th grade akl students at gondang smk. This socialization method goes through four stages, namely the planning, coordination, implementation, and evaluation stages. The material was delivered by the author using a presentation method, question and answer session and a quiz related to the material presented. Based on the results of the service activities that have been carried out at SMK Gondang regarding the socialization of financial management to 10th grade Accounting students, it can be concluded that students can understand the material presented, but most students have not implemented financial management properly. This is based on the quiz answers regarding financial management, almost all of them are correct. This socialization was carried out in accordance with the plan that had been designed. Because all 10th grade Accounting students were directly involved in the activity, with a responsive and enthusiastic state following the activity from start to finish. The socialization of financial management is expected to increase students' knowledge of the importance of financial management. and students can utilize or maximize the money they have.